Unraveling the dynamics of wheat leaf blight complex: isolation, characterization, and insights into pathogen population under Indian conditions - Aditya, Sanghmitra; Aggarwal, Rashmi; Bashyal, Bishnu Maya; Gurjar, Malkhan Singh; Saharan, Mahender Singh; Aggarwal, Shweta (Frontiers in Microbiology, 2024)
Wheat, a staple food crop for 35% of the global population, faces a threat from Helminthosporium leaf blight (HLB), a complex of spot blotch (Bipolaris sorokiniana) and tan spot (Pyrenophora-tritici-repentis) diseases under warm and humid conditions. However, in Indian conditions, the knowledge of existing pathogen populations associated with HLB complex is limited and largely dominated by only B. sorokiniana (spot blotch). To address this, diseased samples were collected from all 6 wheat growing zones during 2020-2022. The pathogenic species were identified through in-depth morphological characterization, supplemented with ITS-rDNA and GAPDH sequence analysis, diagnostic SCAR marker and pathogenicity studies on two wheat varieties; Sonalika and HD2733. The 32 isolates collected from 10 different states consists of B. spicifera (12.5% of all isolates), Exserohilum rostratum (9.3%), Bipolaris oryzae (3.1%) and B. sorokiniana (75%). B. sorokiniana exhibited highest disease severity on both varieties. Other lesser-known pathogenic species also produced comparable disease severity as B. sorokiniana isolates, therefore are economically important. Unravelling pathogen composition and biology aids in disease control and resistance breeding. Our study highlights economically impactful and lesser-known pathogenic species causing wheat leaf blight/spot blotch in India, guiding both current management and future resistance breeding strategies in plant pathology.